Count Olaf’s Antisocial Personality Disorder in Handler’s a Series of Unfortunate Events - Fadhilah Atikah (Lexicon, 2013)
This research discusses the psychological condition of the central character of Daniel Handler’s novel The Series of Unfortunate Events. The focus on this research is to identify and analyze Count Olaf’s personality disorder.This research applies psychological theory from the Diagnostic and Statistical Manual of Mental Disorders, fourth edition (DSM-IV-TR). To support the analysis, the library research method and analytical descriptive method are applied alongside with supported articles, interviews, and reliable website.The result of this research shows that Count Olaf has a personality disorder called antisocial personality disorder. Antisocial personality disorder is also known as psychopathy, sociopathy, or dyssocial personality.